2005
DOI: 10.1152/ajpregu.00544.2003
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure power within frequency range ∼0.4 Hz in rat conforms to self-similar scaling following spinal cord transection

Abstract: This study quantified the effect of interrupting the descending input to the sympathetic preganglionic neurons on the dynamic behavior of arterial blood pressure (BP) in the unanesthetized rat. BP was recorded for approximately 4-h intervals in six rats in the neurally intact state and in the same animals after complete spinal cord transection (SCT) between T(4) and T(5). In the intact state, power within the frequency range of 0.35-0.45 Hz was 1.53 +/- 0.38 mmHg(2)/Hz (mean +/- SD by fast Fourier transform). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…This is consistent with previous studies in humans (Claydon and Krassioukov, 2007;Houtman et al, 2000;Inoue et al, 1991;Munakata et al, 2001), and likely reflects injury to descending sympathetic pathways (Randall et al, 2005), and consequent loss of tonic sympathetic drive to the key resistance and capacitance vessels in the splanchnic vascular bed in those with high-level SCI (Claydon and Krassioukov, 2007;Inoue et al, 1991). Accordingly, hypotension was apparent in animals with T3 SCI, but not in those with T10 SCI.…”
Section: Frequency Analyses Can Distinguish Between Animals With Highsupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with previous studies in humans (Claydon and Krassioukov, 2007;Houtman et al, 2000;Inoue et al, 1991;Munakata et al, 2001), and likely reflects injury to descending sympathetic pathways (Randall et al, 2005), and consequent loss of tonic sympathetic drive to the key resistance and capacitance vessels in the splanchnic vascular bed in those with high-level SCI (Claydon and Krassioukov, 2007;Inoue et al, 1991). Accordingly, hypotension was apparent in animals with T3 SCI, but not in those with T10 SCI.…”
Section: Frequency Analyses Can Distinguish Between Animals With Highsupporting
confidence: 90%
“…We, and others, have observed this resting hypotension in rodents with chronic high-level SCI (Laird et al, 2006), and in people with SCI (Claydon and Krassioukov, 2007;Claydon et al, 2006;Mathias, 2006). One other study examined LF SAP in rodents after acute (up to 1 week) high-level SCI and found a similar reduction in LF SAP (Randall et al, 2005). It is interesting that the LF oscillations in SAP were markedly reduced, but not abolished, in the T3 SCI animals.…”
Section: Frequency Analyses Can Distinguish Between Animals With Highsupporting
confidence: 52%
“…Interestingly, the 0.4 Hz rhythm conforms to the same self-similar behavior characteristic of lower frequencies after interruption of sympathetic outflow via spinal cord transection between T 4 and T 5 (Randall, et al, 2005). From this we concluded “that 1) an intact sympathetic nervous system endows that portion of the power spectrum centered around ~0.4 Hz with properties (e.g., a periodicity) that differ significantly from the self-similar behavior that characterizes the lower frequencies and 2) even within the relatively high frequency range at 0.4 Hz self-similarity is the ‘default’ condition after sympathetic influences have been eliminated” (Randall, et al, 2005). If so, it appears that sympathetic control of the circulation was functionally intact through 6 months of diabetes in this animal model, even during the behavioral changes attendant to transitioning from light to dark and vice versa .…”
Section: Discussionmentioning
confidence: 55%
“…Spectral analysis has been applied to examine blood pressure variation in rats with acute SCI. 70 At 1 and 6 days after complete transection at T4-T5, rats exhibited reduced power in the low-frequency range, indicative of reduced sympathetic tone (or increased parasympathetic tone 85 ) that affects blood pressure control. There are currently no data applying spectral analysis to more chronic experimental SCI.…”
Section: Short-term Cardiovascular Assessment Using Fluid-filled Cannmentioning
confidence: 99%